1984
DOI: 10.1002/j.1460-2075.1984.tb01787.x
|View full text |Cite
|
Sign up to set email alerts
|

Human fibronectin: molecular cloning evidence for two mRNA species differing by an internal segment coding for a structural domain.

Abstract: Two different fibronectin (FN) mRNA species were detected in the human cell line Hs578T. One species, mRNA I, contains an additional 270 nucleotide long insert (ED) that encodes exactly one of the internally repeated structural domains of the protein. The 90 amino acid extra domain belongs to the so‐called type III homology and it is located in the carboxy‐terminal half of FN, in between the cell attachment and the heparin binding sites of the protein. The evidence of two mRNAs is provided by the isolation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
108
1
2

Year Published

1984
1984
1997
1997

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 219 publications
(116 citation statements)
references
References 28 publications
5
108
1
2
Order By: Relevance
“…Previous studies (8,9) have suggested that the ED segment seems to be absent in the hepatocyte mRNAs, which are the source of plasma FN, and it is probable that the inclusion of Here we show that the expression of the IIICS sequence introduces into the FN molecule a region that is susceptible to thermolysin cleavage. This agrees with previous indications of a different susceptibility to proteolytic enzymes in the COOH-terminal region of the two FN subunits (2,11,15,20,23,24,26).…”
Section: Discussionsupporting
confidence: 48%
“…Previous studies (8,9) have suggested that the ED segment seems to be absent in the hepatocyte mRNAs, which are the source of plasma FN, and it is probable that the inclusion of Here we show that the expression of the IIICS sequence introduces into the FN molecule a region that is susceptible to thermolysin cleavage. This agrees with previous indications of a different susceptibility to proteolytic enzymes in the COOH-terminal region of the two FN subunits (2,11,15,20,23,24,26).…”
Section: Discussionsupporting
confidence: 48%
“…Recent studies using monoclonal antibodies have emphasized the heterogeneity of laminin in different sites in embryonic and adult tissues (Wan et al, 1984). This raises the possibility that the laminin molecule synthesized in the brain is different from the basement membrane laminin and that variants or isoforms of laminin, similar to those described for fibronectin (Tamkun et al, 1984;Kornblihtt et al, 1984), exist and exert the different functions. In this context, I note a previous report by Bignami et al (1984) saying the laminin-positive structures in rat embryonic brain are confined to the external basal laminae and the blood vessels.…”
Section: Resultsmentioning
confidence: 99%
“…Double-stranded cDNA containing the 177-basepair Pst IIPst I fragment coding for the EDA portion of FN was excised from cDNA clone p F H l l l (12). This was ligated into pGEM4Z plasmid (Promega, Madison, WI).…”
Section: Methodsmentioning
confidence: 99%